Ansigtsstillingens symbolbetydning i danske kalkmalerier: En gennemgang af syv udsmykninger fra 1100-tallet til 1522 - Haastrup, Ulla (Hikuin, 2007)
Symbolic facial positions By Ulla Haastrup A value-laden symbolic imagery was used for at least 500 years in the wall paintings in Denmark. From the end of the 11th century until the start of the 16th century, faces were only painted in three positions. The most common was the three-quarters face, which was used for the majority of the people in the motifs. Full profile was a little rarer, evil individuals were painted in profile, and toward the end of the Middle Ages, grotesque figures were painted in this way as well. The most important facial position – used for the divine – was the frontal full-face or »en face«. Up until the 14th century, it was only used for God and Christ in Majestas-like motifs and usually it would be painted in the East/West axis of the church. Later on full-face would also be used for mockery faces and grotesque figures as an insult to the divine, the world turned upside down. This traditional symbolic system is of course in no way similar to the real world, as little as the ancient Egyptian art of using the profile in all situations is. We all experience in our daily life and in movies that people move around, so their faces are constantly viewed from new angles and perspectives. If two people are talking, they usually face each other in profile, other people walk and sit in three-quarters face or are viewed from behind. One way of showing faces from the Middle Ages still lives on in the 21st century. An example could be when the TV-speaker speaks to the viewers. When he/she reads aloud, it is common to see the speaker full-face. If the wrong camera is on, it is very common that the speaker apologize to the audience for being in a wrong position, three-quarters face or profile. Then the correct camera shows the speaker en face. The symbol of full-face is here neutral; the speaker does not represent his/her own words or opinions. The »en face« is no longer a symbol of the divine. Around 1960 I described, in my master’s degree thesis in history of art, the late-gothic wall painting workshop, »Isefjordsværkstedet«, how the simple painters – who did not paint the facial features as emotional expressions – used the three facial systems as a significant symbolic sign. To sum it up: Full-face is the divine, three-quarters face the generalized posture of the head of the ordinary neutral person and profile is symbolizing the evil person. This issue has been an interest to me for many years since then, and in 1999 I published an article claiming the importance of the use of these positions of the faces and the symbolic meaning in the presentations of the Jews in the Danish art in the Middle Ages. To clarify the three facial positions in Danish wall paintings more concrete and statistically, I have analyzed seven Danish churches with big decorations. Full-face is unusually frequent in the Romanesque church of Måløv, because the meander frieze includes several icon looking half figures in full-face. In the church of Skive, 1522, the symbolic system has been broken, so that both »en face« and profile are used for saints. The five other monuments show the main trend.